Tropical Sceneries, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
A picture of a variety of tall tropical trees scattered about and in the centre, the tallest of them.
Colour; Sepia; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trees